The impact of teaching in my style of guided discovery and explanation The illustration is developing some physical abilities and skills Volleyball basic (Journal of the College of Basic Education, 2022)
The research included the first chapter and included the definition of the research, the introduction and the importance of the research. The research aims to:- Recognize the effect of using the teaching method, guided discovery and illustrative signs in developing teaching.Some physical abilities and basic skills in volleyball